Increased knowledge of thalassemia promotes early carrier status examination among medical students - Dewanto, Julius Broto; Tansah, Haryono; Dewi, Sari Puspa; Napitu, Helena; Panigoro, Ramdan; Sahiratmadja, Edhyana (Universa Medicina, 2015)
BACKGROUNDThalassemia is an autosomal recessive genetic disorder, in which the patient requires life-long blood transfusion. As Indonesia harbors 6 to 10% thalassemia carriers, thalassemia prevention measures such as early screening and education in the community are urgently needed. The aim of this study was to explore the knowledge, attitude and practice about thalassemia among young medical students. METHODSA cross-sectional analytic observational study was conducted on 179 subjects in 2015, using a questionnaire with items on knowledge, attitude and practice about thalassemia for data collection. After signing informed consent, the questionnaire was filled in by the students and a blood test was performed when the students agreed to be examined. Detection of probable thalassemia carrier status was done by determination of hemoglobin, mean corpuscular volume and mean corpuscular hemoglobin. RESULTSThe knowledge about thalassemia of the first year medical students (n=179) was good (21.1%), moderate (70.9%) and poor (21.1%). Only 67 (38.3%) of the students agreed to a blood examination for determination of their carrier status after filling-in the questionnaire. The knowledge of thalassemia among first year medical students was statistically related to the timing when they would agree to have their thalassemia carrier status examined (p=0.021, one way ANOVA test). CONCLUSIONA higher thalassemia knowledge score causes medical students to be willing to undergo thalassemia carrier status examination at an earlier point in timing. A well-organized educational program focusing on thalassemia and early screening in young adults may enhance the thalassemia prevention program.